The Per Jacobsson Lecture 2006 : Competition Policy and Monetary Policy; A Comparative Perspective. (per Jacobson lecture, 2006)
This chapter provides a comparative perspective of competition policy and monetary policy. Monetary policy and competition policy are two key components of public policies needed for a market economy to function well, and indeed to exist, just as money and the market are two defining elements of such an economy. According to Mario Monti, monetary policy and competition policy compared is that they both serve in different ways the same objective, or at least they have one objective in common, even though their practitioners may not always realize it, and that is price stability. Monetary policies in most countries have been largely successful in recent periods in achieving their objectives, and in some parts of the world, maybe in Europe specifically, this has been facilitated by a number of positive supply shocks, including the setting in motion of conditions in the real economy of greater flexibility and also the creation of the single market, the tearing down of barriers, and the creation and maintenance of competitive conditions.